Establishment of an In Vitro Co-Culture Model of the Piglet Gut to Study Inflammatory Response and Barrier Integrity - Schott, Theresa; Reisinger, Nicole; Teichmann, Klaus; König, Jürgen; Ladinig, Andrea; Mayer, Elisabeth (Planta Medica, 2021)
In intensive farming, piglets are exposed to various challenges that activate intestinal inflammatory processes, negatively affecting animal health and leading to economic losses. To study the role of the inflammatory response on epithelial barrier integrity, co-culture systems that mimic in vivo complexity are more and more preferred over cell monocultures. In this study, an in vitro gut co-culture model consisting of intestinal porcine epithelial cells and porcine peripheral blood mononuclear cells was established. The model provides an appropriate tool to study the role of the inflammatory response on epithelial barrier integrity and to screen for feed and food components, exerting beneficial effects on gut health. In the established model, inflammation-like reactions and damage of the epithelial barrier, indicated by a decrease of transepithelial electrical resistance, were elicited by activation of peripheral blood mononuclear cells via one of 3 stimuli: lipopolysaccharide, lipoteichoic acid, or concanavalin A. Two phytogenic substances that are commonly used as feed additives, licorice extract and oregano oil, have been shown to counteract the drop in transepithelial electrical resistance values in the gut co-culture model. The established co-culture model provides a powerful in vitro tool to study the role of intestinal inflammation on epithelial barrier integrity. As it consists of porcine epithelial and porcine blood cells it perfectly mimics in vivo conditions and imitates the inter-organ communication of the piglet gut. The developed model is useful to screen for nutritional components or drugs, having the potential to balance intestinal inflammation and strengthen the epithelial barrier integrity in piglets.
Keywords: gut health; intestinal inflammation; intestinal porcine epithelial cells; porcine blood cells; oregano oil; licorice extract